2005
DOI: 10.1039/b507457f
|View full text |Cite
|
Sign up to set email alerts
|

Homochiral oligopeptides generated via an asymmetric induction in racemic 2D crystallites at the air–water interface; the system ethyl/thio-ethyl esters of long-chain amphiphilic α-amino acids

Abstract: N(epsilon)-stearoyl-lysine-ethyl-ester (C18-OE-Lys) operates as an efficient desymmetrizing agent for the generation of homochiral oligopeptides via a reaction catalyzed by silver ions in two-dimensional (2D) quasi-racemic crystallites of the corresponding thio-ester (C18-TE-Lys) self-assembled on water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A regular and ordered insoluble monolayer can be utilized as a template to induce water-soluble solutes to form threedimensional crystals at the air/liquid interface (Birman et al, 2010;Weissbuch et al, 2003Weissbuch et al, , 2009Plaut et al, 2003;Rubinstein et al, 2005;Stripe et al, 2012;Frey et al, 1996). However, these insoluble amphiphiles may introduce complications owing to their influence on the interfacial crystallization (Stripe et al, 2012), unfavorable for understanding the relationship between the molecular structure of the crystallizing material and the resulting crystal morphology and properties.…”
Section: Introductionmentioning
confidence: 99%
“…A regular and ordered insoluble monolayer can be utilized as a template to induce water-soluble solutes to form threedimensional crystals at the air/liquid interface (Birman et al, 2010;Weissbuch et al, 2003Weissbuch et al, , 2009Plaut et al, 2003;Rubinstein et al, 2005;Stripe et al, 2012;Frey et al, 1996). However, these insoluble amphiphiles may introduce complications owing to their influence on the interfacial crystallization (Stripe et al, 2012), unfavorable for understanding the relationship between the molecular structure of the crystallizing material and the resulting crystal morphology and properties.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, when the reaction was initiated with Ag + ions, or mixtures of I 2 /KI were inserted into the aqueous solution, it occurred preferentially between molecules of the same handedness along the translation a-axis (Figure 8.2d,e), to yield isotactic diastereoisomers. The racemic composition of the isotactic peptides could be desymmetrized by addition of the corresponding enantiopure ethyl esters, as these esters form 2-D quasi-racemates with the thioesters by being incorporated within the rows of thioesters of the same handedness [31]. The results of these studies showed that the esters operate not only as efficient initiators but also as chain terminators of the peptides of opposite absolute configuration.…”
Section: Isotactic Oligomers Generated Within Monolayers At the Air-wmentioning
confidence: 65%
“…The results of these studies showed that the esters operate not only as efficient initiators but also as chain terminators of the peptides of opposite absolute configuration. This yields shorter chains with a different composition, in contrast to the isotactic chains, which grow unperturbed [31].…”
Section: Isotactic Oligomers Generated Within Monolayers At the Air-wmentioning
confidence: 99%
“…Advanced analyses of surface monolayers with high sensitivity techniques such as polarized infrared reflection-adsorption spectroscopy [50] and Brewster angle microscopy combined with GIXD technique [51] will assist the progress of this research field especially if combined with theoretical approaches based on computational modeling and energy calculations [52,53]. Several possible outcomes other than the often proposed sensor uses must be given serious consideration, while purposes related to nonlinear optics [54] and surface reactions [55,56] have already been reported for chiral monolayers. However, an important goal for subsequent research is chiral recognition involving the unique characteristics of the air-water interface.…”
Section: Resultsmentioning
confidence: 99%